2013
DOI: 10.12930/nacada-13-015
|View full text |Cite
|
Sign up to set email alerts
|

Advising and Progress in the Community College STEM Transfer Pathway

Abstract: Community college students enrolled in science and technology fields face many challenges as they pursue transfer pathways to earn a 4-year degree. Despite clear links to student persistence, advising interactions that facilitate or inhibit transfer progress are not clearly understood. In this study, 82 community college students pursu ing science and technology transfer-based pro grams of study participated in phenomenological interviews. Students described how professors, major advisors, and transfer office … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 24 publications
1
45
0
Order By: Relevance
“…With the guidance provided by the advisors, international students gained a better understanding about their academic journey in community college and pathways to baccalaureate degrees. These findings echoed previous research (Bai & Pan, 2009;Campbell & Nutt, 2008;Hunter & White, 2004;Packard & Jeffers, 2013) that academic advising plays an integral role in students' learning and, when it is done well, it promotes students' transition to and adjustment in a new learning environment. These findings may encourage administrators and academic advisors to continue strengthening their advising practice in community colleges.…”
Section: Academic (In)validationsupporting
confidence: 85%
“…With the guidance provided by the advisors, international students gained a better understanding about their academic journey in community college and pathways to baccalaureate degrees. These findings echoed previous research (Bai & Pan, 2009;Campbell & Nutt, 2008;Hunter & White, 2004;Packard & Jeffers, 2013) that academic advising plays an integral role in students' learning and, when it is done well, it promotes students' transition to and adjustment in a new learning environment. These findings may encourage administrators and academic advisors to continue strengthening their advising practice in community colleges.…”
Section: Academic (In)validationsupporting
confidence: 85%
“…Accordingly, it is important that two-year colleges offer resources to help women increase their knowledge about transfer into four-year STEM programs, through intentional and proactive academic and transfer advising that helps illuminate viable transfer pathways (Packard et al, 2012; Packard and Jeffers, 2013). In her qualitative study, Jackson (2013) found that interpersonal exchange, such as consistent communication and information sharing within the community, as opposed to solitary activities (e.g., looking up information online), is the major venue through which Black two-year college women prepare for upward transfer and gain career knowledge in STEM fields.…”
Section: Implications For Policy and Practicementioning
confidence: 99%
“…Consistent with past literature on advising (Broadbridge, 1996;Christian & Sprinkle, 2013), guidance was the most commonly reported theme of positive advising experiences in our study. Prior research also showed that students prefer developmental advising, in which the advisor gets to know each advisee's needs and collaborates with the student in the advising process (e.g., Hollis, 2009), and that students appreciate advisors who actively listen and offer relevant referrals (Packard & Jeffers, 2013). These themes underscore the importance of student-focused communication strategies rather than the provision of information alone.…”
Section: Discussionmentioning
confidence: 99%